Reception par de Directoire - Motte, Charles Etienne Pierre, 1785-1836 (lithographer):::Creator::::::::::::; Boulanger (artist):::Contributor::::::::::::; Bosio, Jean François, 1764-1827 (artist):::Contributor:::::::::::: (France; Chez Émile Babeuf; Paris)
Lithograph of Napoleon being received by the Directory in Paris, part of a series of prints by Charles Motte depicting the life of Napoleon.